2022
DOI: 10.1038/s41467-022-31252-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of negative feedback for persistent epithelial cell–cell junction contraction by p21-activated kinase 3

Abstract: Actin-mediated mechanical forces are central drivers of cellular dynamics. They generate protrusive and contractile dynamics, the latter of which are induced in concert with myosin II bundled at the site of contraction. These dynamics emerge concomitantly in tissues and even each cell; thus, the tight regulation of such bidirectional forces is important for proper cellular deformation. Here, we show that contractile dynamics can eventually disturb cell–cell junction contraction in the absence of p21-activated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Schematic illustration, adapted from refs. [28, 39] (D) Time‐lapse images of remodeling cell–cell junctions labeled with myosin II (GFP‐tagged myosin II regulatory light chain) in the A8a epithelia. Orange and green arrows, shortening and extending junctions, respectively.…”
Section: The Mechanism Underlying Cell–cell Junction Shorteningmentioning
confidence: 99%
See 4 more Smart Citations
“…Schematic illustration, adapted from refs. [28, 39] (D) Time‐lapse images of remodeling cell–cell junctions labeled with myosin II (GFP‐tagged myosin II regulatory light chain) in the A8a epithelia. Orange and green arrows, shortening and extending junctions, respectively.…”
Section: The Mechanism Underlying Cell–cell Junction Shorteningmentioning
confidence: 99%
“…[ 34,36–38 ] Live‐imaging of the Pak3 mutants at a cellular resolution and semi‐quantification revealed that cell rearrangement was perturbed during the A8a movement, specifically at the step of cell–cell junction shortening; although junctions initiated shortening, they failed to complete it and instead re‐extended, resulting in repetition of shortening and extension of the same cell–cell contacts. [ 28 ]…”
Section: The Mechanism Underlying Cell–cell Junction Shorteningmentioning
confidence: 99%
See 3 more Smart Citations